Śrī. Bra. Yo. Sītārāma Mahārāja Ṭembye yāñce ovībaddha caritra - Vidṽāsa, Jānakībāī (Bra. Yo. Sītārāma Mahārāja Ṭembye Sãsthāna, 1973)
Verse work on Sītārāma Mahārāja Ṭembye, 1857-1917, a Hindu saint from Maharashtra, India.